The Importance of the Cultural and Gender Outlook on Consumer Behavior Studies: An Indonesian Perspective - Ari Riswanto; Euis Saribanon; Vanessa Gaffar (Arthatama: Journal of Business Management and Accounting, 2018)
The Indonesian Core Value with Gender Sub Culture - Study of Consumer Behavior, is a study in the field of marketing management, which is discussed in depth using the library method using various reference sources, including books, journals and other related sources, in addition, direct observation is also carried outed in order to find facts in the community. The purpose of this study is to find out the value the core of Indonesia is seen from the cultural and gender perspective on consumer behavior. Finally, hopefully this study will be a benefit in developing marketing management research specifically related to consumer behavior.